2018
DOI: 10.1097/wnr.0000000000001109
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the frontal alpha asymmetry indicators of habitual emotion regulation

Abstract: Frontal alpha asymmetry (FAA) has been explored extensively in affective neuroscience. To determine which FAA indicators are linked with the habitual use of emotion regulation, we recorded the resting electroencephalogram alpha activity. First, we reduced all of the FAA indicators to four factors by exploratory factor analysis. Next, we carried out a multiple regression analysis to determine which factors could significantly predict the habitual use of emotion-regulation strategies. According to the results, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…A positron emission tomography study (Kim et al, 2012) revealed that greater left-sided bias in metabolic activity at the dorsolateral prefrontal cortex is associated with frequent use of a cognitive reappraisal strategy. Greater left prefrontal cortex activations likewise predict frequent use of cognitive reappraisal strategies (Wang et al, 2018). High FAA scores at the prefrontal electrode pairs (FP2-FP1) have been shown to predict the fluency and flexibility in generating cognitive reappraisals (Papousek et al, 2017).…”
Section: Effect Of Negative Emotion Differentiation On Frontal Alpha mentioning
confidence: 99%
See 1 more Smart Citation
“…A positron emission tomography study (Kim et al, 2012) revealed that greater left-sided bias in metabolic activity at the dorsolateral prefrontal cortex is associated with frequent use of a cognitive reappraisal strategy. Greater left prefrontal cortex activations likewise predict frequent use of cognitive reappraisal strategies (Wang et al, 2018). High FAA scores at the prefrontal electrode pairs (FP2-FP1) have been shown to predict the fluency and flexibility in generating cognitive reappraisals (Papousek et al, 2017).…”
Section: Effect Of Negative Emotion Differentiation On Frontal Alpha mentioning
confidence: 99%
“… Goodman et al (2013) reported that individuals with high FAA showed a higher spontaneous emotion regulation ability under high-stress situations. Wang et al (2018) found that high FAA at the prefrontal cortex is associated with the frequent use of cognitive reappraisal. Resting FAA is also related to emotion regulation ability in children as reported by their parents ( Hannesdottir et al, 2010 ) and cognitive reappraisal ability in anger-eliciting events ( Perchtold et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%
“…Frontal alpha asymmetry (FAA), i.e. asymmetry of alpha power between the left and right frontal region, has been linked with emotional processing ( Davidson et al, 1990 ), emotional control ( Sun et al, 2017a ; Wang et al, 2018 ) and vulnerability to depression ( Gotlib et al, 1998 ). However, in a recent review resting-state FAA was found to have a limited diagnostic value in depression partly due to the high degree of heterogeneity across studies ( van der Vinne et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, high FAA at the prefrontal cortex is associated with the frequent use of cognitive reappraisal. 53 Therefore, the FAA was calculated in this study as a neuro-electrophysiological and objective indicator to assess participants' emotional regulatory ability and the choice of reappraisal. And we predicted that the IA group might show lower FAA compared with the HC group due to the maladaptive emotion regulation choice.…”
Section: Introductionmentioning
confidence: 99%